2001
DOI: 10.1074/jbc.m009517200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis through B-cell Receptor Cross-linking Occurs via de Novo Generated C16-Ceramide and Involves Mitochondria

Abstract: B-cells, triggered via their surface B-cell receptor (BcR), start an apoptotic program known as activationinduced cell death (AICD), and it is widely believed that this phenomenon plays a role in the restriction and focusing of the immune response. Although both ceramide and caspases have been proposed to be involved in AICD, the contribution of either and the exact molecular events through which AICD commences are still unknown. Here we show that in Ramos B-cells, BcR-triggered cell death is associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
120
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(133 citation statements)
references
References 46 publications
10
120
2
Order By: Relevance
“…Previous studies have shown that ceramide has a direct proapoptotic effect on the mitochondrial cascade. 7,8,25 Overall, these findings led us to investigate the involvement of BEX2 in the mitochondrial apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that ceramide has a direct proapoptotic effect on the mitochondrial cascade. 7,8,25 Overall, these findings led us to investigate the involvement of BEX2 in the mitochondrial apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10]25 To investigate this we first carried out a mitochondrial permeability transition (MPT)-based apoptosis assay, which detects changes in…”
Section: Bex2 Protects the Breast Cancer Cells Against Mitochondrial mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, previous studies have shown that de novo generated ceramide in response to stimulation of the BcR receptor in B cells results in selective accumulation of C 16 -ceramide (23), and this was implicated in the apoptotic response of those cells (24). On the other hand, activation of neutral SMase2 was shown to selectively induce the formation of C 24 -ceramide and C 24:1 -ceramide, and evidence was provided for a role for this pathway in cell cycle regulation (25) and in interleukin-6 formation (26).…”
Section: Discussionmentioning
confidence: 99%
“…8,9) The hydrolysis of SM by SMase appears to be a major route for the generation of Cer in response to stimuli such as cytokines, antibodies, steroids, and heat shock, 3,10,11) although de novo synthesis of Cer is also increased by stimuli. 12) Cer can be further processed to sphingosine by ceramidase (CDase) and then to sphingosine 1-phosphate by sphingosine kinase. The latter product is a well-known ligand for G-protein-coupled receptors S1P 1-5 .…”
mentioning
confidence: 99%